Missing Food : The Case of Postharvest Grain Losses in Sub-Saharan Africa - World Bank (Washington, DC, 2012)
Low-income, food-deficit countries have become especially concerned about the global and national food situation over the past three years. While the proximate cause of this heightened concern was the surge in food prices that began in 2006 and peaked in mid-2008, concerns remain for other reasons, among them the higher market-clearing price levels that now seem to prevail, continuing price volatility, and the risk of intermittent food shortages occurring repeatedly far into the future. For lower-income Sub-Saharan Africa (SSA) countries, ongoing contributing factors include persistently low productivity, difficulty adapting to climate change, financial difficulties (inability to handle the burden of high food or fuel prices or a credit squeeze), and increased dependence on food aid. Yet there is an additional, often-forgotten factor that exacerbates food insecurity: postharvest losses (PHL). They can and do occur all along the chain from farm to fork, which reduces real income for all consumers. This especially affects the poor; as such a high percentage of their disposable income is devoted to staple foods. This report is based on the desk study undertaken by experts of the U.K. Natural Resources Institute (NRI). Data were collected by direct contact (e-mail or telephone), with authorities holding information on past and current projects; by searching the Internet for details about projects; and by reviewing published and 'gray' literature. Data were also collected from the personal experiences of the NRI review team who had worked on numerous and diverse projects to reduce grain PHL in SSA over the last 30 years and from experts in the field. These experts were identified and asked to complete a questionnaire that would draw out their experiences to indicate the weakest links in the postharvest chain, the interventions that deserve to be prioritized for future action, and those that should be avoided. Of about 40 invited respondents, a total of 20 returned completed (or partially completed) questionnaires.